Fostering Well‐being through Social Support: The Role of Evangelical Communities in the Lives of Dominican Women of Haitian Descent. Issue 1 (20th October 2020) - Salusky, Ida; Tull, Mary; Case, Andrew D.; Soto‐Nevarez, Arturo
Abstract: Women of Haitian descent living in the Dominican Republic experience oppression due to their gender, ethnicity, and economic status. They also exhibit high rates of participation in evangelical Christian communities, a paradoxical finding given the restricted roles women have traditionally played in these settings. The goals of this study were to explore the perceived benefits of participation in evangelical communities and the setting characteristics that lead to these benefits. The research team interviewed 19 current and former church participants aged 18–59. Thematic analysis revealed three perceived benefits of congregational life. Participants viewed their participation as: (a) an opportunity for personal growth and development; (b) protective against negative social influences; and (c) providing social support in the face of life challenges. In addition, dependable, expected, and reciprocal relational support was a key characteristic of evangelical communities. Findings extend the current understanding of how religious communities enhance well‐being for marginalized women through social support networks. Findings also explore the dialectical nature of settings as both empowering and disempowering. Implications for future interventions are discussed. Highlights: Religious communities can provide social support for women marginalized at multiple levels. Greater religious involvement over time predicts social support. Religious communities can facilitate positive identity narratives despite negative cultural messages. Rules and structure of organized religious life can protect against community risk. Religious spaces can simultaneously foster well‐being and create vulerability for women.